PERBAIKAN SIFAT-SIFAT DAN PENCEGAHAN HIDROFOBISITAS TANAH GAMBUT DI PERKEBUNAN KELAPA SAWIT MELALUI APLIKASI TERAK BAJA - Winarna Winarna; Iput Pradiko; Muhdan Syarovy; Fandi Hidayat (Pusat Penelitian Kelapa Sawit, 2016)
Development of oil palm plantation on peatland was faced with hydrophobicity problem caused by over drained. Hydrophobicity could reduce water retention and nutrient availability in the peat soil. Beside of proper water management application, addition of soil ameliorant which contain iron could increase stability and improve peat soil fertility. The study was conducted to obtain the effect of steel slag on peat soil properties and hydrophobicity. In this study, peat soil was incorporated with steel slag and incubated in 60 days period. The research was employed completely randomized design (CRD) factorial 2 x 2 x 4. First factor is peat maturity consists of two levels: sapric (S) and hemic (H), while the second factor is soil moisture which also consist of two levels: field capacity (W1) and dry (under the critical water content) (W2). The third factor is steel slag dosage which consist of four levels: 0 g pot (TB0), 7.17 g pot (TB1), 14.81 g -1 -1 pot (TB2), and 22.44 g pot (TB3). The result showed that application of steel slag significantly increase of soil pH, ash content, and water retention at pF 4.2. Furthermore, application of steel slag significantly reduce time for water reabsorption (wettability) in sapric. On the other hand, there are negative corellation between water penetration and soil pH, ash content, and water retention at pF 4.2. Overall, application of steel slag could increase wettability and prevent peat soil hydrophobicity.